2017
DOI: 10.5999/aps.2017.44.4.313
|View full text |Cite
|
Sign up to set email alerts
|

Non-Melanocytic Skin Cancers of the Head and Neck: A Clinical Study in Jeju Province

Abstract: BackgroundJeju Island is geographically and socioeconomically distinct from the mainland of South Korea. Thus, the presentation and management of non-melanocytic skin cancers (NMSC) of the head and neck may differ from those in other regions of the country. We compared the clinical characteristics and treatment modalities of NMSC on Jeju Island with the findings of similar regional studies. MethodsPatient data, including age, sex, diagnosis, tumor site, treatment, and recurrence, were obtained from the medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Our 3-year LFFS rate was 91.7% ( Fig. 1), which was similar to that previously reported for radiotherapy [8] and comparable to data regarding the surgical treatment of basal and squamous cell skin cancers in the head and neck region [18]. Treatment options for BCC and SCC skin cancers in the head and neck region include surgical excision and radiotherapy.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our 3-year LFFS rate was 91.7% ( Fig. 1), which was similar to that previously reported for radiotherapy [8] and comparable to data regarding the surgical treatment of basal and squamous cell skin cancers in the head and neck region [18]. Treatment options for BCC and SCC skin cancers in the head and neck region include surgical excision and radiotherapy.…”
Section: Discussionsupporting
confidence: 89%
“…Cosmetic outcomes were mostly excellent or good. Kang et al [18] reported 120 patients with BCC or SCC of the face treated with surgery, obtaining a 98% local control rate.…”
Section: Discussionmentioning
confidence: 99%
“…SCC, the second recorded common NMSC, is of keratinocyte origin. 9 It involves the trunk and other body parts 10 and is mainly categorized histologically as well, moderately or poorly differentiated. 11 …”
Section: Introductionmentioning
confidence: 99%
“…Their combination may increase long term efficacy and reduce surgical removal, especially on sun exposed areas, with excellent cosmetic results, increasing patient's compliance (Cantisani et al, 2012;Micali et al, 2014). Recent studies have suggested an increased incidence of NMSC in women (Kang, Yun, Song, & Shin, 2017). This could be attributed to women's increasing longer average life expectancy and the consequent increased exposure to UV rays.…”
mentioning
confidence: 99%